2010
DOI: 10.1111/j.1365-2648.2010.05262.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reasoning: concept analysis

Abstract: This concept analysis provides a middle-range descriptive theory of clinical reasoning in nursing that helps clarify meaning and gives direction for future research. Appropriate instruments to operationalize the concept need to be developed. Research is needed to identify additional variables that have an impact on clinical reasoning and what are the consequences of clinical reasoning in specific situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
234
1
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(253 citation statements)
references
References 39 publications
(44 reference statements)
2
234
1
16
Order By: Relevance
“…The definition of clinical reasoning is often associated with critical thinking, clinical judgment and decisionmaking (6) , without making it explicit to the reader which adopted understanding of the concept it is within each study. This situation by itself weakens the integration of results from different research, which is characterized as one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of clinical reasoning is often associated with critical thinking, clinical judgment and decisionmaking (6) , without making it explicit to the reader which adopted understanding of the concept it is within each study. This situation by itself weakens the integration of results from different research, which is characterized as one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reasoning is a generic term that is commonly referred to as the processes through which information is obtained and interpreted to draw the necessary conclusions for health care. However, other expressions are used interchangeably with clinical reasoning, such as clinical judgment, decision-making process or even critical thinking (5)(6) . Regardless, clinical reasoning is a primary skill in nursing practice because it is through it that professionals identify, prioritize, and establish plans, as well as interpret clinical data (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Nicklin & McVeety (2002) found that Canadian nurses perceived that healthcare environment uncertainty jeopardize patient safety. Also (Simmons, 2010;Penrod, 2007;and Rabey, 2006) found that experiencing clinical uncertainty put patient safety and their quality of care at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The process of clinical reasoning is multifarious and clinicians of all levels of ability and experience look to develop the cognitive elements of decision-making to enhance practice and improve patient-care (Benner 1984;Higgs 1992;Neistadt 1996). This synthesising process involves considering many facets of patient data, clinician experience, clinician knowledge, and the literature (Higgs and Jones 2008;Simmons 2010). This interactive process then further evidences the clinical decision (Childs et al 2003;Curran et al 2006;Doody & McAteer 2002;Noll et al 2001;Orme & Maggs 1993).…”
Section: Introductionmentioning
confidence: 99%